2008
DOI: 10.1021/je700633w
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Gallic Acid in Methanol, Ethanol, Water, and Ethyl Acetate

Abstract: The solubility of gallic acid in methanol, ethanol, water, and ethyl acetate was measured at a temperature range of (298.2 to 333.2) K. The gallic acid solubility in different solvents increases smoothly with temperature. The relative solubility of gallic acid in the solvents was found as: w methanol > w ethanol > w water > w ethyl acetate . The temperature dependence of the solubility data was correlated by the modified Apelblat model. The calculated solubilities show good agreement with the experimental data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
104
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 15 publications
11
104
0
1
Order By: Relevance
“…It was observed that an increase in the temperature increased the solubility of GE, EA, and GA, regardless of the solvent used (Table 7). A similar observation was reported by Daneshfar et al (2008), whereby the solubility of gallic acid in different solvents increased correspondingly with increasing temperature.…”
Section: Equilibrium Solubility In Biorelevant Mediasupporting
confidence: 87%
See 1 more Smart Citation
“…It was observed that an increase in the temperature increased the solubility of GE, EA, and GA, regardless of the solvent used (Table 7). A similar observation was reported by Daneshfar et al (2008), whereby the solubility of gallic acid in different solvents increased correspondingly with increasing temperature.…”
Section: Equilibrium Solubility In Biorelevant Mediasupporting
confidence: 87%
“…The solubility of GE, EA, and GA was observed to be the highest in intestinal fluids (SIF: pH 6.8, FaSSIF: pH 6.5, and FeSSIF: pH 5) and the least in gastric fluid (SGF: pH 1.2). This could be due to the acidic nature of the compounds (Ascacio-Valdes et al, 2011;Daneshfar et al, 2008;Przewloka & Shearer, 2002).…”
Section: Equilibrium Solubility In Biorelevant Mediamentioning
confidence: 99%
“…In contrast to the compounds mentioned below, gallic acid is highly soluble in water and in polar solvents such as ethanol or methanol (Daneshfar et al 2008). This compound is found in hornbeam and oak bark, oak apple, green or black tea, hops, pomegranate and in other plants and fruits.…”
mentioning
confidence: 99%
“…This suggests that either AA is a stronger antioxidant than the GA or that the concentration of GA is too low to scavenge free radicals in the solution [7]. Indeed, the applied GA concentration was only 1% (w/w), but this is the maximal achievable concentration in water solution at room temperature [3]. The T 1 dependence on antioxidant concentration has been already studied in the previous work [5] for AA and glutathione additives, the recovery of T 1 relaxation time was found to be more effective at higher concentrations of these antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidants applied were ascorbic acid (AA, vitamin C, Polskie Odczynniki Chemiczne, POCH Poland) and gallic acid (GA, Fluka Chemika Switzerland), which were used as saturated water solutions at the concentrations of 17% (w/w) and 1% (w/w), respectively [2,3].…”
Section: Methodsmentioning
confidence: 99%